Stress as Mediator of Organizational Culture and Learning Organizations on Work Achievement of PT. Kazeto Putra Perkasa Employees - Manurung, Antonius Dieben Robinson; Triputra, Dimas Ramdani (Dinasti Publisher, 2024)
The Covid-19 pandemic has occurred almost all over the world and has become a new problem for all mankind, as well as Indonesia has been affected from the Covid-19 pandemic. The impact of the Covid-19 pandemic has had an impact on various sectors, especially on educational institutions. The Covid-19 pandemic situation puts a lot of pressure and new challenges in the world of education. This can cause instability for both employees from various aspects, one of which is the aspect of employee performance. Based on a number of literatures, work achievement is influenced by several other variables, namely; organizational culture, organizational learning and stress. This study uses a quantitative approach with Structural Equation Modeling (SEM) – SmartPLS. The subjects in this study were all employees of PT. Kazeto Putra Perkasa with 101 employees. The sampling technique used in this study is a saturated sample, where the entire population is used as the research sample. The practical implication of this research is that it is known how important work achievement is as a key indicator of success for both employees of PT. Kazeto Putra Perkasa as well as for companies, the importance of understanding stress from concept to application is mainly related to how to manage stress, as well as the implementation of organizational culture and learning organizations as a concept that affects work achievement with stress as a mediator.